ECOMANAGE – INTEGRATED ECOLOGICAL COASTAL ZONE MANAGEMENT SYSTEM - Deliverables 2.6 & 2.8 - Argentina: D2.6 - SIG mapping of hydrogeologic parameters, including groundwater recharge asessment and vulnerability to pollution, D2.8 - Groundwater flow and transport components of the global estuary model (2nd Part: Bahía Blanca estuary) - Oliveira, M. M. (2008)
Bahía Blanca case study area comprises three watersheds that discharge in the estuary, near Bahía Blanca city, from west to east: Sauce Chico, Saladillo and Napostá Grande. The total area is 3,915 km2. The study area is included in the Colorado basin that is characterized by faulted bedrock which affects the Paleozoic substratum. Since tertiary age no significant faults occur and the overlying sediments were deposited with a gentle slope towards the centre of the basin in a syneclise structure. The pedologic description is based on the Soil Map of the Buenos Aires Province of the Argentine Republic. From the pedologic description of the soils and their properties, the information required to run the sequential daily water balance models and to characterize the S parameter of the DRASTIC index of groundwater vulnerability to pollution was derived. Land use is of major importance to characterize the depth of the soil subject to the evapotranspiration and to define the ability of a determined area to produce direct runoff. Both these informations are also needed for the sequential daily water balance models. These models allow the computation of the direct runoff, real evapotranspiration and deep percolation processes. Deep percolation is an estimator of groundwater recharge. A detailed description of these sequential daily water balance models is presented. Two methods were applied, (A) one, included in the BALSEQ_MOD program, that computes direct runoff using the soil properties and the real evapotranspiration using the dual crop coefficient approach, and (B) another, included in the BALSEQ program, which computes direct runoff using the land use/soil properties and the real evapotranspiration assuming a constant crop coefficient. Both methods require the computation of the potential evapotranspiration. The potential evapotranspiration is computed using the reference evapotranspiration and the crop coefficients. Daily climate data recorded in Bahía Blanca Aerodrome is used. This data was processed and missing data were filled. Also the precipitation from this climate station was used. For each land cover unit the crop coefficients were determined and presented. Another method used to estimate groundwater recharge is the separation of the surface flow hydrograph. This method, included in the DECHIDR_VB program, is described and is applied to the Cerro del Águila stream flow gauge station, in the upper Napostá Grande watershed. From the applied methodologies, the BALSEQ method provided the best results: average precipitation = 723 mm.year-1, real evapotranspiration = 631 mm.year-1, average direct runoff = 27 mm.year-1, average recharge = 61 mm.year-1. Finally, groundwater discharge to the estuary, as determined in Heffner (2003), is only 2,000 m3.d-1, a value that represents less than 1 mm.year-1 if the total watershed area is considered.